2011
DOI: 10.2139/ssrn.1970039
|View full text |Cite
|
Sign up to set email alerts
|

Self Control and Liquidity: How to Design a Commitment Contract

Abstract: If individuals have self-control problems that lead them to spend money when they had previously planned to save it, they may take up financial commitment devices that restrict their future ability to access their funds. We experimentally investigate how the demand for commitment contracts is affected by contract design features. In our experiments, each subject is endowed with a sum of money and asked to divide that money between a liquid account, which permits unrestricted withdrawals at any time over the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 55 publications
1
45
1
1
Order By: Relevance
“…People with low self-control put too much weight on the near future disregarding long-term costs and benefits. For example, DellaVigna and Malmendier (2006) find that most people plan to attend the gym on a regular basis when signing the membership contract, but actual attendance is much lower (for further evidence on self-control problems see DellaVigna, 2009;Beshears et al, 2011). One way to overcome these problems is to bind or precommit one's own behavior (see for example Strotz, 1955;Thaler and Shefrin, 1981;Laibson, 1997;Sorger, 2007).…”
Section: Hyperbolic Discountingmentioning
confidence: 99%
See 1 more Smart Citation
“…People with low self-control put too much weight on the near future disregarding long-term costs and benefits. For example, DellaVigna and Malmendier (2006) find that most people plan to attend the gym on a regular basis when signing the membership contract, but actual attendance is much lower (for further evidence on self-control problems see DellaVigna, 2009;Beshears et al, 2011). One way to overcome these problems is to bind or precommit one's own behavior (see for example Strotz, 1955;Thaler and Shefrin, 1981;Laibson, 1997;Sorger, 2007).…”
Section: Hyperbolic Discountingmentioning
confidence: 99%
“…1) By introducing a commitment device allowing people to bind or precommit their behavior (see Strotz, 1955). If people choose the lump sum because of self-control problems a precommitment device is a powerful tool to help people overcome this problem (see for example Thaler and Shefrin, 1981;Laibson, 1997;Beshears et al, 2011). 2) Making it mandatory to determine the payout scheme at the beginning of the contract when people are (still) young and not at retirement, is another way to increase real life annuitization rates.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, past research has demonstrated that people value mechanisms that prevent their future selves from making unwise decisions such as procrastinating (Ariely and Wertenbroch 2002), undersaving (Ashraf et al 2006, Beshears et al 2011, smoking cigarettes (Giné et al 2010), failing to achieve workplace goals (Kaur et al 2010), and giving in to repeated temptations in the laboratory (Houser et al 2010). Study participants have expressed a willingness to use "commitment devices" such as placing money in restrictive accounts that prevent premature savings withdrawals (Ashraf et al 2006, Beshears et al 2011; self-imposing deadlines with associated late penalties to prevent procrastination on coursework (Ariely and Wertenbroch 2002); and placing money on the line for forfeiture if they fail to quit smoking, exercise, or lose weight (Halpern et al 2012, John et al 2012, Royer et al 2012, Volpp et al 2008.…”
Section: Utility Utilitymentioning
confidence: 99%
“…Study participants have expressed a willingness to use "commitment devices" such as placing money in restrictive accounts that prevent premature savings withdrawals (Ashraf et al 2006, Beshears et al 2011; self-imposing deadlines with associated late penalties to prevent procrastination on coursework (Ariely and Wertenbroch 2002); and placing money on the line for forfeiture if they fail to quit smoking, exercise, or lose weight (Halpern et al 2012, John et al 2012, Royer et al 2012, Volpp et al 2008.…”
Section: Utility Utilitymentioning
confidence: 99%
See 1 more Smart Citation